Outcome of phacoemulsification in eyes with cataract and corneal opacity partially obscuring the pupillary area - Panda, A; Krishna, S N; Dada, T (Nepalese Journal of Ophthalmology, 2012)
Objective: To evaluate the intra-operative difficulties and postoperative visual outcome following phacoemulisification and intraocular lens (IOL) implantation in eyes with cataract and a coexisting corneal opacity partially obscuring the pupillary area. Materials and methods: The study included 205 eyes of 205 patients with cataract, an extensive corneal opacity partially obscuring the pupillary area and a corrected distance visual acuity (CDVA) of less than 40/200 who had undergone phacoemulisification with IOL implantation by a single surgeon. The patients were followed up on day 1, day 7, 1 month and 3 months postoperatively. Intra-operative and post operative course and CDVA were evaluated. Results: Seventy nine percent of the patients underwent phaco-emulsification via superior clear corneal approach while the rest were operated via temporal clear corneal approach. Trypan blue (0.06%) dye assisted capsulorrhexis was successfully completed in all eyes with additional maneuvers including posterior synechiolysis and sphincterotomy. Nucleotomy with primary chop technique and phacoemulsification were performed uneventfully in all but one eye, which was converted to an extra capsular cataract extraction (ECCE). A foldable intraocular lens was implanted in 76 eyes, rigid IOL in 128 eyes and 1 eye was left aphakic. The pre-operative CDVA of less than 40/200 improved to 20/60 at the end of 3 months follow up.Conclusions: Phacoemulsification and intraocular lens implantation provides ambulatory and useful vision in eyes with coexisting cataract and corneal opacity.DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6535 Nepal J Ophthalmol 2012; 4 (2): 217-223